Immune Optimization as a Preventive and Therapeutic Adjunct for the Management of Renin–Angiotensin–Aldosterone System Dysfunction Diseases: A Review - Michael T. Okafor; Queenet C. Onyebuchukwu; Germaine A. Okafor; Samuel C. Niteh; Chikere A. Anusiem (International Journal of Medicine and Health Development)
Renin–angiotensin–aldosterone system (RAAS) dysfunction affects all systems of the body with an array of symptoms and their management is challenging. Immune dysfunction provokes their pathogenesis and clinical symptoms. Hence, immune optimization interventions may be useful for their prevention and management. This review aimed to discuss the putative T cell and RAAS dysfunction-mediated model of diseases using their dysfunction in disease phenotypes as classic examples. Online searches on databases, such as Google Scholar, PubMed, Biomed Central, and SciELO, were carried out. We reviewed articles with keywords, such as Renin Angiotensin Aldosterone System, Immune-Mediated Inflammatory Diseases, Immune Dysfunction, T lymphocyte activation/dysfunction, cytokines, RAAS Dysfunction, RAAS blockers, therapeutic adjunct, and prevention. Disease mechanisms underlying putative RAAS dysfunction T cell-mediated diseases were discussed. Immune optimization as a preventive and therapeutic adjunct for RAAS dysfunction T cell-mediated diseases was also discussed. Immune optimization could serve as a preventive and therapeutic adjunct for the management of RAAS dysfunction-mediated diseases.